2018
DOI: 10.1021/acsami.8b14790
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Conjugated Magnetite Nanoparticles as a Promising Drug Delivery System for Targeted Thrombolysis: Synthesis and Preclinical Evaluation

Abstract: Mortality and disabilities as outcomes of cardiovascular diseases are primarily related to blood clotting. Optimization of thrombolytic drugs is aimed at the prevention of side effects (in particular, bleeding) associated with a disbalance between coagulation and anticoagulation caused by systemically administered agents. Minimally invasive and efficient approaches to deliver the thrombolytic agent to the site of clot formation are needed. Herein, we report a novel nanocomposite prepared by heparin-mediated cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 60 publications
1
69
0
4
Order By: Relevance
“…16,23,72 There have been several reports of tPA and other thrombolytic drugs being bound to various types of nanoparticles, including iron oxide nanoparticles, with characterization and testing in vitro and in rodents using non-rotating magnets. 22,57,[73][74][75][76][77][78][79][80][81][82][83][84] It has recently been reported that polyacrylic acid -coated tPA -MNPs have been successfully tested in vitro and in a mouse model of embolic stroke, in which a rotating magnetic field was employed. 21 TPA has also been transported to blood clots in vitro and to clots in mice femoral arteries, using a rotating magnetic system.…”
Section: Discussionmentioning
confidence: 99%
“…16,23,72 There have been several reports of tPA and other thrombolytic drugs being bound to various types of nanoparticles, including iron oxide nanoparticles, with characterization and testing in vitro and in rodents using non-rotating magnets. 22,57,[73][74][75][76][77][78][79][80][81][82][83][84] It has recently been reported that polyacrylic acid -coated tPA -MNPs have been successfully tested in vitro and in a mouse model of embolic stroke, in which a rotating magnetic field was employed. 21 TPA has also been transported to blood clots in vitro and to clots in mice femoral arteries, using a rotating magnetic system.…”
Section: Discussionmentioning
confidence: 99%
“…As in other fibrinolytic particles discussed previously, encapsulating or immobilizing PA on MNP increases enzyme stability during storage and improves half‐life . Magnetic nanoparticles carrying tPA, uPA, or SK have been decorated with coatings that further improve half‐life and reduce immunogenicity including dextran, chitosan, silica, hydrosol, PLGA and PLA‐PEG, polyacrylic acid (PAA), PEG, poly[aniline‐co‐N‐(1‐one‐butyric acid) aniline], and heparin . Plasminogen activator functionalization of MNP can rely on either physical adsorption to the MNP matrix or covalent attachment .…”
Section: Magnetic Particles and Magnetic Field Controlmentioning
confidence: 99%
“…79 Magnetic nanoparticles carrying tPA, uPA, or SK have been decorated with coatings that further improve halflife and reduce immunogenicity including dextran, 80,81 chitosan, 82 silica, 79,83 hydrosol, 84 PLGA and PLA-PEG, 85 polyacrylic acid (PAA), 86 PEG, 87,88 poly[aniline-co-N-(1-one-butyric acid) aniline], 78 and heparin. 89 Plasminogen activator functionalization of MNP can rely on either physical adsorption to the MNP matrix or covalent attachment. 90 Adsorption yields high concentrations of tPA (>20 μg/mL) near a thrombus 85 however, PA desorbs from PLGA, PAA, and uncoated magnetite rods within 30 min of injection.…”
Section: Synthesis and Functionalization Of Magnetic Nanoparticle Cmentioning
confidence: 99%
“…[1][2][3][4][5] In medical sciences, nanostructures with magnetic properties have become particularly interesting for potential application in diagnosis, drug delivery, cell separation, thrombolysis and cancer treatment. [6][7][8][9][10][11] Preferred are particles below 20 nm diameter due to enhanced tissular diffusion in this size regime. 12 Iron-based nanostructures have been studied thoroughly for applications as magnetic agents.…”
Section: Introductionmentioning
confidence: 99%